Wedge resection plus adequate lymph nodes resection is comparable to lobectomy for small-sized non-small cell lung cancer - Ding, Hongdou; Song, Nan; Zhang, Peng; Jiang, Gening; Wang, Haifeng (Frontiers in Oncology, 2022)
Objectives The study investigated whether wedge resection plus adequate lymph nodes resection conferred comparable overall survival (OS) to lobectomy for node-negative non-small cell lung cancer (NSCLC) ≤2 cm. Methods The Surveillance, Epidemiology, and End Results database was used to identify patients diagnosed with NSCLC ≤2 cm and underwent wedge resection or lobectomy (2004-2015). Patients were stratified by the procedure (wedge resection, lobectomy) and the size of NSCLC (≤1 cm, 1-2 cm). We assessed OS between patients undergoing wedge resection and lobectomy. The optimal number of lymph nodes resected which made those two procedures comparable was explored by using Kaplan-Meier analysis and Cox regression analysis. Propensity score matching was performed to minimize the effect of confounding factors. Results 7893 patients with lobectomy and 2536 patients with wedge resection were identified. Wedge resection was associated with worse OS either in the ≤1 cm or 1-2 cm NSCLC before and after matching. For lesions 1-2 cm and receiving lobectomy, more lymph nodes resected conferred statistically significant increase on OS and six nodes were optimal. For lesions ≤1 cm and receiving lobectomy, lymph nodes resection had no impact on OS. Wedge resection and lobectomy were comparable when one or more nodes for lesions ≤1 cm and six or more nodes for lesions 1-2 cm were resected. Conclusions Wedge resection was inferior to lobectomy for NSCLC ≤1 cm and 1-2 cm. Wedge resection plus adequate number of resected lymph nodes was comparable to lobectomy.